2020
DOI: 10.25073/jaec.202044.306
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Automatic Skin Lesions Diagnosis-A Deep Learning Ensembling Approach

Abstract: Skin is the largest organ of the human body, it protects them from the external environment. However, the number of new skin cancer cases has been going up in the last few years. Fortunately diagnosing skin cancer in earlier stages could increase the probability of treating cancer. Due to machine learning (ML) and deep learning(DL) has achieved great success in different fields and has shown an outstanding performance in computer vision applications, lots of ML Applications is concerned in this domain. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The same data set is used with cross‐validation in a previous study 45 and found that there are no biased subsets. In this study, the dataset is divided into two sets only, a training set with 8012 samples and a testing set with 2003 samples whereas the testing set will be held to the end to ensure evaluation of the proposed model within new data.…”
Section: Methodsmentioning
confidence: 99%
“…The same data set is used with cross‐validation in a previous study 45 and found that there are no biased subsets. In this study, the dataset is divided into two sets only, a training set with 8012 samples and a testing set with 2003 samples whereas the testing set will be held to the end to ensure evaluation of the proposed model within new data.…”
Section: Methodsmentioning
confidence: 99%